Inhibition of glycogen synthase kinase 3 beta (GSK3β) suppresses the progression of esophageal squamous cell carcinoma by modifying STAT3 activity. Issue 10 (4th July 2017) - Gao, Shegan; Li, Shuoguo; Duan, Xiaoxian; Gu, Zhen; Ma, Zhikun; Yuan, Xiang; Feng, Xiaoshan; Wang, Huizhi
Abstract : Although GSK3β has been reported to have contrasting effects on the progression of different tumors, it's possible functions in esophageal squamous cell carcinoma (ESCC) and the related molecular mechanisms remain unknown. Here, we investigated the expression, function, and molecular mechanism of GSK3β in the development of ESCC in vitro and in vivo. Though the expression of total GSK3β was significantly increased, the phosphorylated (inactivated) form of GSK3β (Ser9) was concurrently decreased in the cancerous tissues of patients with ESCC compared with controls, suggesting that GSK3β activity was enhanced in cancerous tissues. Further pathological data analysis revealed that higher GSK3β expression was associated with poorer differentiation, higher metastasis rates, and worse prognosis of ESCC. These results were confirmed in different ESCC cell lines using a pharmacological inhibitor and specific siRNA to block GSK3β. Using a cancer phospho‐antibody array, we found that STAT3 is a target of GSK3β. GSK3 inhibition reduced STAT3 phosphorylation, and overexpression of constitutively active GSK3β had the opposite effect. Moreover, STAT3 inhibition mimicked the effects of GSK3β inhibition on ESCC cell migration and viability, while overexpression of a plasmid encoding mutant STAT3 (Y705F) abrogated these effects, and these results were further substantiated by clinicopathological data. In addition, a GSK3 inhibitor (LiCl) and/or STAT3 inhibitor (WP‐1066) efficiently suppressed the growth of ESCC cells in a xenograft tumor model. Altogether, these results reveal that higher GSK3β expression promotes ESCC progression through STAT3 in vitro and in vivo, and GSK3β‐STAT3 signaling could be a potential therapeutic target for ESCC treatment.